2017
DOI: 10.1111/cod.12690
|View full text |Cite
|
Sign up to set email alerts
|

Atypical and severe airborne isothiazolinone contact dermatitis mimicking Kaposi–Juliusberg syndrome

Abstract: A 14-year-old boy with a history of mild atopic dermatitis (AD) was referred with an acute and extensive facial eruption.Physical examination showed erythematous and vesicular lesions, some of which were clearly umbilicated and agglomerated (Fig. 1a), located on the face, neck, and distal forearms, including very oedematous eyelids. Cervical lymphadenomegaly was observed, but no mucosal involvement, respiratory symptoms or fever were present. Superinfection of his AD with herpes simplex virus (HSV) was suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In Europe, contact dermal exposure to CMIT/MIT has been of significant concern [27,28]. In addition to dermal exposure via direct contact, cases of concern with respect to airborne products (e.g., paint) have been reported with some patients exhibiting asthmatic symptoms [27,29]. Limited inhalation toxicity studies using rats have shown lung redness and inflammation at high doses [30,31].…”
Section: Estimation Of Atmospheric Concentration Of Cmit/mitmentioning
confidence: 99%
“…In Europe, contact dermal exposure to CMIT/MIT has been of significant concern [27,28]. In addition to dermal exposure via direct contact, cases of concern with respect to airborne products (e.g., paint) have been reported with some patients exhibiting asthmatic symptoms [27,29]. Limited inhalation toxicity studies using rats have shown lung redness and inflammation at high doses [30,31].…”
Section: Estimation Of Atmospheric Concentration Of Cmit/mitmentioning
confidence: 99%
“…Undisclosed presence was noted in adhesive labels, leading to ACD of the exposed fingers [ 96 ], partially airborne ACD after using ironing water preserved with MI in 4 British patients [ 97 ], soothing and cooling gel pads applied to the lower lids during application of lash extensions [ 98 ], airborne ACD accompanied by a dry cough in a construction worker [ 99 ], (partly airborne) ACD due to a stainless steel cleaning spray [ 100 ], foot dermatitis due to a shoe glue preserved with MI [ 101 ], occupational ACD in two gynaecologists due to MI in ultrasound gel [ 102 ], chronic dermatitis of the trunk and proximal extremities in a 7-year-old girl due to liquid laundry detergent [ 103 ], although it has been claimed, based on a small study, that MI cannot be detected in the laundered fabric [ 104 ]. Newly painted rooms, with airborne exposure to MI for several weeks, is a well-known cause of elicitation of ACD by MI [ 85 , 105 , 106 , 107 ], partly leading to very severe and atypical clinical presentations [ 108 ]. The need of a complete declaration of MI (and all isothiazolinones) has been illustrated by the case of a 9-year-old boy with widespread airborne ACD where a (online accessible) product data sheet informed about the presence of MI, MCI, and BIT and thus the cause was found [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides MI, also BIT is often present in water-based paints. 25,51,54 Isothiazolinone derivatives: a review Several atypical clinical manifestations elicited by isothiazolinones have been described: systemic ACD from BIT after inhalation via airborne exposure 46,55 ; nummular eczema in a housepainter 56 ; lupus erythematosus-like eruptions 57 ; 'lymphomatoid' dermatitis 44,57,58 ; Kaposi-Juliusberg syndrome-like rash in a boy 37 and following exposure to paints 59 ; lichenoid eruptions; also a flare-up of a long-standing oral lichen planus, after the erroneous use of a dishwashing liquid for a dental prosthesis 60 ; and scalp lesions mimicking folliculitis decalvans due to a MI-containing hair gel. 61 A combination of urticarial and eczematous skin eruptions has been frequently observed, although Type I hypersensitivity, confirmed by positive prick tests, has never been reported.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Several atypical clinical manifestations elicited by isothiazolinones have been described: systemic ACD from BIT after inhalation via airborne exposure; nummular eczema in a housepainter; lupus erythematosus‐like eruptions; ‘lymphomatoid’ dermatitis; Kaposi–Juliusberg syndrome‐like rash in a boy and following exposure to paints; lichenoid eruptions; also a flare‐up of a long‐standing oral lichen planus, after the erroneous use of a dishwashing liquid for a dental prosthesis; and scalp lesions mimicking folliculitis decalvans due to a MI‐containing hair gel …”
Section: Clinical Aspectsmentioning
confidence: 99%